3D modified wavelet block tree coding for hyperspectral images - Shrish Bajpai; Harsh Vikram Singh; Naimur Rahman Kidwai (Institute of Advanced Engineering and Science, 2019)
A novel wavelet-based efficient hyperspectral image compression scheme for low memory sensors has been proposed. The proposed scheme uses the 3D dyadic wavelet transform to exploit intersubband and intrasubband correlation among the wavelet coefficients. By doing the reconstruction of the transform image cube, taking the difference between the frames, it increases the coding efficiency, reduces the memory requirement and complexity of the hyperspectral compression schemes in comparison with other state-of-the-art compression schemes.